2001
DOI: 10.3346/jkms.2001.16.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Cephalic spreading levels after volumetric caudal epidural injections in chronic low back pain

Abstract: The volumetric caudal epidural steroid injection has been advocated to facilitate the delivery of medications to the lesion site. This study was aimed to examine the actual spreading patterns of this technique, using epidurogram. A total of 32 patients with chronic low back pain accompanied by radiculopathy of various causes (degenerative spondylosis, herniated nucleus pulposus, spondylolisthesis, and spinal stenosis) were included. The volumetric caudal epidural injection of the 10 mL mixture of contrast medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 0 publications
0
18
0
2
Order By: Relevance
“…Kim et al documented epidurographically that a 10-mL solution bolus reaches far enough to mid and lower lumbar area, and extra volumes or repeated injections could not significantly change the blocked level 19. We used a 10-mL corticosteroid bolus for injection of the interlaminar epidural space.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al documented epidurographically that a 10-mL solution bolus reaches far enough to mid and lower lumbar area, and extra volumes or repeated injections could not significantly change the blocked level 19. We used a 10-mL corticosteroid bolus for injection of the interlaminar epidural space.…”
Section: Discussionmentioning
confidence: 99%
“…Although the sacral epidural space is largest it also has the greatest amount of leakage [9]. Kim et al [7] showed that the mid to lower lumbar region of the spine could be consistently treated using caudal epidurals of up to 30 ml. There was no change in the levels attained by subsequent injections.…”
Section: Discussionmentioning
confidence: 99%
“…Volumetric caudal injections have been examined by epidurography by Kim et al [7] who found no advantage in terms of cephalic migration of injectate, despite using incremental volumes up to 50 ml. They suggest that improved clinical outcome may be a result of mechanical forces generated intradurally and epidurally by the larger volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Les anesthésiques locaux bloquent aussi les fibres afférentes C de la nociception [3,7]. L'infiltration peut agir en faisant disparaître les adhérences et les cicatrices qui peuvent survenir en réponse à l'agression tissulaire, et qui peuvent comprimer les structures nerveuses [8,9]. L'effet volume lié à l'infiltration agit comme tuyau d'arrosage fournissant un jet dans une conduite bouchée dans le but de la dégager [8, 10,11].…”
Section: Discussionunclassified